Contar para não esquecer: uma análise dos passados presentes na militância feminina em “Que bom te ver viva” - Valaci, Silvia Fioravante Guimarães de Carvalho (2022)
This work seeks to discuss memory relations through the narratives of eight former female militants who went through torture, rape, kidnapping and other atrocities during the period of Brazilian civil-military dictatorship (1964-1985). Such narratives are present in the cinematographic work “Que Bom Te Ver Viva”, released in 1989, under the direction of the filmmaker Lúcia Murat, in which it highlights the political participation of women in the dictatorial period who, due to this, were tortured, silenced and many socially erased, since her image was associated only with care and submission to her home, husband and children. In this sense, this study aims to understand and discuss the representation of the feminine through the context of memorialistic and historiographical production about the military dictatorship, with regard to testimonial narratives, social identity and the past-present relationship of the former militants in the film. by Lucia Murat. To this end, it is evident how 20th century literature, taken as testimonial literature, dialogues with the theme to be addressed in the methodological process of this work, since the filmmaker also went through the same processes as the women present in this documentary work. experienced. The character's monologue, whose name is not revealed, portrays, through lapses of memory in dialogue with specific situations of his speech, the atrocities lived and a possible lack of identity in view of the erasure of the former militants, however, it is noticeable how there is an identity in the struggle, especially in the testimonies presented. From this perspective, there is mention of the past-present relationship, that is, what was experienced is a historical reality that marks the existence of these women and, in addition, there is a mention of how these events express the “after”, which is the the way you react or the way you choose to live.